Pengembangan Sistem Informasi Ticketing untuk Pengadaan Barang dengan Algoritme Analytic Hierarchy Process untuk Prioritas berbasis Web (Studi Kasus PT. Kawasaki Motor Indonesia) - Samuel Arthur; Faizatul Amalia; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Kawasaki Motor Indonesia has an information system division that regulates all matters related to IT. This division also procures goods for IT goods. However, this division has a problem that is the filing process is still done manually and conventionally which results in paper that has been filled manually must still be delivered to the information system division room even though the company has a very wide area and the existing divisions are separated by sufficient distance far. The company also wants to reduce paper usage. Another thing that is a problem is sometimes the information system division is also confused to decide which work should take precedence. Therefore, research is carried out to solve this problem and produce a web-based information system in the form of ticketing for procurement of goods and provide an Analytic Hierarchy Process (AHP) algorithm to help make decisions. The system was developed using the waterfall model approach. The results obtained are the system produces 25 functional needs and 1 non-functional requirement which are then tested using unit testing and validation testing which produces 100% valid. Testing non-functional requirements were tested using a sortsite application for compatibility and resulted in a system that could be used in various web browsers. The system is also tested using User Acceptance Testing (UAT) which produces a value of 100% based on the given task. Accuracy testing is done by comparing the ranks of experts and systems that produce an accuracy of 66.6667%.